Students' Satisfaction and Self-Efficacy in Arabic Teacher Education Using SPACE and Zoom Platforms in Education 5.0. - Raswan, Raswan; Wahab, Muhbib Abdul; Qodri, Muhammad; Mustar, Mustar; Busri, Hasan (Ijaz Arabi Journal of Arabic Learning, 2025)
This study investigates the levels of satisfaction and self-efficacy among student-teachers enrolled in the Arabic Teacher Professional Education Program, focusing on the impact of SPACE and Zoom-based online learning environments within the context of the 5.0 era. Understanding how these changes affect teacher preparation is crucial as educational paradigms shift towards more technologically integrated methods. Utilizing a mixed-methods approach, data were collected from 82 student-teachers at LPTK Islamic University in Jakarta, Indonesia, through surveys and interviews. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data underwent thematic analysis. The findings indicate high levels of satisfaction and self-efficacy among participants, with Zoom-based learning showing a slightly higher preference over SPACE-based learning. Factors contributing to these outcomes include the flexibility, accessibility, and interactive nature of the online platforms. However, students were found to be less familiar with Learning Management Systems (LMS), which impacted their motivation to develop advanced productive skills in speaking and writing. The study underscores the importance of leveraging advanced technological tools to enhance teacher training programs and recommends comprehensive training and tutorials for student teachers. Additionally, it suggests that educators assign productive tasks, particularly in speaking and writing scientific articles in Arabic, to optimize online learning experiences in the era of Education 5.0. These insights are invaluable for policymakers, educators, and institutions that foster effective and adaptive teacher education models.